2007
DOI: 10.1016/j.chemosphere.2007.06.041
|View full text |Cite
|
Sign up to set email alerts
|

Well water contaminated by acidic mine water from the Dabaoshan Mine, South China: Chemistry and toxicity

Abstract: An investigation into well water quality was carried out in a rural area subject to irrigation with acidic mine water from the Guangdong Dabaoshan Mine, southern China. The results of water pH measurements from 112 wells in two different seasons suggest that the well water has been contaminated to varying degrees in the investigated Shangba floodplain (approximately 11 km south of the Guangdong Dabaoshan Mine). There is a trend that well water pH increased southwards, suggesting that the impacts of acidic irri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(19 citation statements)
references
References 7 publications
1
18
0
Order By: Relevance
“…This area has a long history of mining activities, and large scale mining for iron and copper ores has been operated by the state-run Guangdong DaBao Mountain Mining Corporation since 1970s [11]. Now this area is designated as a nationally funded bioremediation site.…”
Section: Source Of Inoculamentioning
confidence: 99%
“…This area has a long history of mining activities, and large scale mining for iron and copper ores has been operated by the state-run Guangdong DaBao Mountain Mining Corporation since 1970s [11]. Now this area is designated as a nationally funded bioremediation site.…”
Section: Source Of Inoculamentioning
confidence: 99%
“…Apart from adverse impacts on the aquatic biota (Cherry et al, 2001;David, 2003;Harris et al, 2003;Gerhardt et al, 2004;Olias et al, 2004;Lin et al, 2007), irrigation of agricultural lands with acidic mine water results in acidification and heavy metal contamination of soils and groundwater in the affected areas (Lin et al, 2005;Chen et al, 2007). Elevated concentrations of heavy metals accompanied with acidic pH are likely to enhance uptake of heavy metals by plants (Boularbah et al, 2006;Li et al, 2007), which poses a high health risk to the people who consume the contaminated agricultural products.…”
Section: Introductionmentioning
confidence: 98%
“…Approximately 15,000 m 3 /day of AMD has been produced by the LWMRD, contaminating surface water, groundwater and soil downstream from the mine. The heavy metal levels detected have been above the limits set in the Chinese National Standards for Drinking Water (Chen et al, 2007), and the average concentrations of Cu, Zn, Cd and Pb in the surrounding soil have all been above the natural soil background levels (Zhao et al, 2012). Zhuang et al (2009) found that the heavy metals accumulated in the food crops (rice and vegetables) grown around the mine posed a serious health risk to the local population.…”
Section: Introductionmentioning
confidence: 99%
“…Heavy metals, including Cd, Co, Cr, Cu, Mn, Ni, Pb and Zn, have the potential to become major contamination sources and are often extremely detrimental to aquatic and soil environments (Anju and Banerjee, 2010;Kim et al, 2009). As a typical poly-metallic mine, and one of the biggest opencast mines in Southern China, the Dabaoshan Mine region in northern Guangdong province was one of the largest copper mining and refining centres during the Song Dynasty (960-1279 AD) (Chen et al, 2007). The Liwu mud-retaining dam (LWMRD), with a capacity of 20 million cubic metres, was constructed in 1979 to retain the waste rock produced by the mine.…”
Section: Introductionmentioning
confidence: 99%